OPTIMIZING VIDEO TRANSMISSION PERFORMANCE IN 5GHZ MANET - QASMARROGY, GHASSAN A. (Journal of Duhok University, 2021)
Nowadays, one of the most important technologies is video transmission. It is used worldwide across multiple platforms such as mobile, tablets, smart watches, and many more. All these devices use the 2.4GHz and 5GHz frequency ranges of IEEE 802.11. Due to the mobility of these devices, it’s very important to optimize video transmission streaming between these mobile devices with minimum delay and higher throughput. In this paper, an attempt will be made to enhance the transmission performance of video over MANET using IEEE 802.11n 5GHz frequency range supported by the new devices. The performance of two famous routing protocols, AODV and OLSR, is compared in terms of delay, throughput, and retransmission attempts.